Language Environment Programs and Students’ Speaking Performance: A Study at One Islamic Boarding School - Shynta Amalia; Badriyah Badriyah; Muhammad Iqbal Ramdhani (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2022)
This study aimed to see the effect of language environment programs which has been common in Islamic boarding school in Jambi, on students speaking performance. Through an ex post facto research design, the researchers would like to find out whether there is a significant difference between the students' speaking performance of those who involve in language environment programs and that of those who do not involve in the programs. Thirty-second graders of As’ ad Senior High Islamic Boarding School were selected purposively as the samples of the study. The results of the independent-sample t-test showed that there was a significant difference in the results of speaking performance for the students who were involved in language environment programs (M= 15.4, SD = 1.08891), and for those who did not involve in language environment programs (M= 9.3, SD= 1.04881; p=0.000). Besides, the students involved in the programs are considered better in terms of fluency than the students who do not involve in the programs.